Nutritional status, individual traits, and disease incidence at An-Nur Boarding School, Surabaya - Zamzam, Maki Zamzam; Herdiani, Novera; Ekiq Kurniavie, Lidia (Universitas Nahdlatul Ulama Surabaya, 2024)
One of the relative impacts caused by nutrition is weakening resistance to diseases that are usually not fatal and improving nutrition is a main factor that helps increase resistance to disease. This research aims to find out the nutritional status, individual characteristics and incidence of disease in students at the An-Nur Islamic Boarding School in Surabaya. The method used in this research is a descriptive method with a quantitative approach and verification method. The population in this study were students at the An-nur Islamic Boarding School, Surabaya. The sample technique used is simple random sampling. The questionnaire has been validated and consists of 4 sections: General information on respondents (characteristics of age, gender, length of time as a student), nutritional status, stress (using the DASS 21 stress section), gastritis (signs and symptoms), and scabies (risk factors and symptom). The results of this research are that the average age of the students is 19.5 years, the majority are women, 50 students, the majority are new students, the nutritional status of most of them is normal, 43 students have a fairly high stress level, 39 students have low levels of gastritis and only 18 students have scabies. low, only 17 students. The conclusion of this research is that most of the students are still young/adolescents, the majority are women, many are new students, the majority have normal nutritional status, high stress levels, low incidence of gastritis and scabies.